MULTIPLE LINEAR REGRESSION ANALYSIS ON THE EFFECT OF EXPORTS AND IMPORTS ON INDONESIA’S FOREIGN EXCHANGE RESERVE 2005-2021 - reni permatasari; Khoirul Anam; Nuari Anisa Sivi; Iskandar Iskandar (Jurnal Statistika Universitas Muhammadiyah Semarang, 2022)
Foreign exchange reserves can be an important indicator to see how far a country can carry out international trade and to show the strength of a country's economic fundamentals. The size of the foreign exchange reserves is influenced by several factors, one of which is export and import activities. This study aims to identify the effect of exports and imports on the position of Indonesia's foreign exchange reserves. The data used are secondary data from the Central Statistics Agency and Bank Indonesia. The object used in this study is Indonesia with Time Series, which is 17 years from 2005 to 2021. This study uses a quantitative approach with the Multiple Linear Regression Analysis method using software the IBM-SPSS Version 25.0. Based on the results of the regression, it is known that the value of exports has a positive and significant effect on Indonesia's foreign exchange reserves, this is indicated by the value of sig 0.000 < 0.050. Meanwhile, imports have a negative and significant effect on Indonesia's foreign exchange reserves, this is indicated by the value of Sig 0.567. sig value 0.567 > 0.050. Export and Import variables together on Indonesia's Foreign Exchange Reserves. This can be seen from the results of the analysis of the significance value (Sig.) 0.00 < 0.050.